Photocorrosion of Cuprous Oxide in Hydrogen Production: Rationalising Self‐Oxidation or Self‐Reduction. Issue 41 (11th September 2018) - Toe, Cui Ying; Zheng, Zhaoke; Wu, Hao; Scott, Jason; Amal, Rose; Ng, Yun Hau
Abstract: Cuprous Oxide (Cu2 O) is a photocatalyst with severe photocorrosion issues. Theoretically, it can undergo both self‐oxidation (to form copper oxide (CuO)) and self‐reduction (to form metallic copper (Cu)) upon illumination with the aid of photoexcited charges. There is, however, limited experimental understanding of the "dominant" photocorrosion pathway. Both photocorrosion modes can be regulated by tailoring the conditions of the photocatalytic reactions. Photooxidation of Cu2 O (in the form of a suspension system), accompanied by corroded morphology, is kinetically favourable and is the prevailing deactivation pathway. With knowledge of the dominant deactivation mode of Cu2 O, suppression of self‐photooxidation together with enhancement in its overall photocatalytic performance can be achieved after a careful selection of sacrificial hole (h + ) scavenger. In this way, stable hydrogen (H2 ) production can be attained without the need for deposition of secondary components. Abstract : This catalyst will self‐destruct in … Photoexcited Cu2 O can photocorrode by two possible pathways; namely, self‐photoreduction into Cu metal or self‐photooxidation into CuO. A systematic study of Cu2 O photocorrosion demonstrates that this process is dominated by self‐photooxidation through consumption of photogenerated holes (h + ). Scale bar: 100 nm.